TURKMENISTAN: CHANGING STATE POWER CONSTRUCTS AND POLITICS - ABDRAKHMANOV, Askar (CENTRAL ASIA AND THE CAUCASUS, 2007)
It is extremely hard to obtain reliable information of any sort about the political developments in Turkmenistan. The ruling regime is too closed to be studied in any detail. The latest events, however, revealed hitherto concealed aspects of Turkmenian policy. President Niyazov’s death created an absolutely new political situation in the country. This was the first time in post-Soviet history that the military and law-enforcement structures represented by the Security Council assumed responsibility for the future of the country and the nation. It acquired its leading role and the right to remove the president and/or chairman of the People’s Council—Khalk Maslakhaty (KM), the parliament— under the constitutional amendments. The changes in the ruling elite that began when KM Speaker O. Ataev was removed from his post to make it possible to nominate G. Berdymukhamedov as presidential candidate were successfully completed when he was elected president; the country also acquired a new Cabinet. On 30 March, the results were confirmed by the election of the new president as chairman of the Khalk Maslakhaty To legitimize their power in the eyes of the nation and the international community, the new leaders eased up on the pressure imposed by the regime and outlined measures designed to improve the people’s standard of living. The new rulers did not hesitate to prevent any form of antigovernment activity and took pains to ensure that political emigrants remained abroad in order to exclude their involvement in Turkmenian politics in the near future.In fact, there is no need to tighten the regime’s grip on power to earn the nation’s respect. The new elite should be more open; it should invite the world to engage in a reasonable and equal dialog; the regime will inevitably be less strict.The new Turkmenian leadership is clearly hoping to improve the country’s international image; it has already started active and dynamic talks with all the interested forces (Russia, the U.S., Iran, China, Kazakhstan, and Azerbaijan). In the absence of any real alternative to the Russian gas export route, Ashghabad will continue improving its relations with the Kremlin, a trend that is already clear under the new conditions. The prospect of new export pipelines is vague because of the highly complicated geopolitical context; it is not yet clear whether the country has enough fuel reserves, in addition to those already sold under long-term contracts.